Pengembangan Media Pembelajaran Papan Hitung pada Materi Penjumlahan dan Pengurangan dalam Meningkatkan Hasil Belajar Fase A SD/MI: Indonesia - Nurhatmi, Jules; Pane, Liska Novi Yanti; Janah, Fitri Roudhatul (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to develop a Counting Board as a learning tool to enhance the understanding of addition and subtraction concepts among Phase A elementary school students (SD/MI). The research employed the Research and Development (R&D) method using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The counting board was validated by media and material experts, resulting in a very valid score (90%) and practical score (88%), supported by a 100% positive response from teachers, indicating the media's high feasibility for classroom use. The implementation involved small group trials (8 students) and large group trials (28 students), with learning outcomes analyzed using the N-Gain Score. The results showed a significant improvement in students' understanding, with a high category score (0.77) in the small group and a moderate category score (0.69) in the large group. Furthermore, 98.46% of first-grade students and 97.9% of second-grade students reported that the counting board motivated and facilitated their learning. These findings demonstrate that the Counting Board is not only valid and practical but also effective in enhancing students' learning outcomes for addition and subtraction concepts.